واقع الاستثمار في القطر العربي السوري وآفاق تطويره - سلمان, حيان (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تُعدُّ الاستثمارات الحامل الاقتصادي الأساسي لتحقيق التنمية العامة الشاملة. فالمشروعات الإستثمارية تساهم في زيادة الإنتاج والإنتاجية مما يؤدى إلى زيادة الدخل القومى وارتفاع متوسط نصيب الفرد منه وبالتالي تحسين مستوى معيشة المواطنين. كما وتسهم في توفير الخدمات والمنتجات للمواطنين وللمستثمرين داخل الدولة وتصدير الفائض منها للخارج مما يوفر العملات الأجنبية اللازمة لشراء الالات والمعدات. كما أن لها دور اساسي في توفير فرص العمل, الى جانب مساهمتها في زيادة معدلات التكوين الرأسمالى للدولة. وانطلاقاً من إدراك الحكومة السورية لهذة الأهمية الإقتصادية للاستثمار, وضعت الاستثمار هدفا ً اقتصادياً وطنيًا وقامت بالعديد من إجراءات الإصلاح الاقتصادي، إلا أنه وعلى الرغم من كل المزايا التي قدمّت للاستثمارات فإنها لم تعط النتائج المتوقعة منها حتى الآن، كما يلاحظ أن قطاع الخدمات والنقل والعقارات يجذب معظم الإستثمارات في حين أن القطاعات الإقتصادية الإنتاجية كقطاع الزراعة والصناعة لا تزال الاستثمارات فيها متواضعة. Investments are the basic economic carrier to achieve the general total development. The investment projects help to increase the production and productivity which leads to the increase of national income, and the rise of the individual's share of it, which leads to improve the level of living. They also help to provide the services and products for the citizens and investors inside the country, and export the surplus which provides the foreign currency necessary to import machinery and equipment. They also have a basic role in providing jobs in addition to increasing the levels of capital formation of the state. Government's awareness of the economic importance of investment led it to put the investment as a national economic target and performed many of the economic reforms. But all these procedures did not give the expected results until now. It can be noticed that the sectors of services, transportation, and real estate attract most of investments, whereas the level of investment in the productive sectors such as agriculture and industry is very low.